Phytosociological evaluation in the atlantic cerrado-matte transition zone (Research, Society and Development, 2020)
The objective of the present work was to characterize the predominant vegetation in a transition area between the Cerrado and Atlantic Forest biomes. Field data collection was performed to obtain the parameters used for floristics and phytososciology: absolute density (AD), relative density (DR), absolute frequency (AF), relative frequency (RF), absolute dominance ( DoA), relative dominance (DoR), importance value index (IVI), coverage value index (IVC), Shannon-Weaver index (H '). We sampled 274 individuals belonging to 21 families, distributed in 44 different species. Of these, 44 we observed predominance of species occurring in the Cerrado and Atlantic Forest biomes corresponding to 40% of the total sampled, followed by species occurring only in the Cerrado biome, with 35% of the total sampled species. Only 15% of the species found are exclusively from the Atlantic Forest biome; and 10% occur in the Cerrado, Atlantic Forest and also in the Pantanal biome. The largest representativeness is present in the Fabaceae family (angicos and aroeira) and Rubiciaea (castle), corresponding to 39% of the sampled individuals, revealing that the studied area has the largest number of species present in the cerrado. As for the Shannon-Weaver index, it presented low floristic diversity (1.35 individual-individuals). The three species with the highest importance value index were the castle, angico Vermelho and aroeira, all species occurring in the Cerrado biome, with 43.7; 39.07 and 29.1 respectively The importance of most species was small considering the values of density, frequency and dominance.